Sentimentos e perspectivas de futuro de usuários de substâncias psicoativas em tratamento em centro de atenção psicossocial para álcool e drogas - Inoue, Laryssa (2012)
The use and abuse of drugs is a health problem highly relevant in current society. In Brazil, up to the 1980s, assistance to individuals with any type of drug dependence occurred exclusively by hospitalization. Through the publishing of Decree 336 in 2002, the Psycho-social Attention Centers - Alcohol and Drugs (Caps-AD) were instituted as a reference service nationwide in the assistance of chemical dependents. Current analysis aims at understanding the experience of psychoactive drug users treated at Caps-ad, their feelings and behavior prior to and posterior to treatment and at investigating the perceptions on life before and after treatment and their future perspectives. Data of current exploratory and qualitative study on 28 drug or ex-drug users were collected between August and September 2012, when treated at Caps-ad. Focal group technique was used with the relevant question "How do you feel being a drug user?" coupled to other questions required for responses to the study. Bardin's Thematic Analysis of Contents was employed for data treatment. Ethical principles that involve research with human beings were respected during the study and the project was approved by the Permanent Committee of Ethics involving Humans of the State University of Maringá (N. 67292/2012). Data analysis identified the feelings and behavior of drug users before and after the treatment for chemical dependence. Pre-treatment life was characterized by sentiments of inferiority, sadness at the loss of family ties, aggressive behavior directed to satisfy the will for drug intake. After start of treatment, individuals highlighted the negative experiences and their sadness with regard to deviant behavior in their past. New type of behavior showed the will to reestablish family ties and obtain support for abstinence. It was evident that treatment helped people to perceive that life had been marked by an inauthentic living and this fact contributed towards the reestablishment of the subjects' identity. They became aware of the loss they experienced during the period in which they consumed drugs and of the need for change. By seeking help at Caps-ad, they re-adapted their lives by accepting limitations, they became aware what motivated them to seek drugs to move to other directions, they perceived their return to the family and projected new routes for their lives. It may be concluded that Caps-ad was highly relevant in the lives of these subjects and their families since they were accepted at the most fragile moment and contributed towards the reconstruction of their lives, according to each case's possibilities.